M24 Prevalence of anxiety and patient characteristics from a randomised controlled trial (RCT) to identify if cognitive behavioural therapy (CBT) by respiratory nurses reduces anxiety in COPD. (12th November 2015) - Heslop-Marshall, K; Baker, C; Carrick-Sen, D; Stenton, SC; Newton, J; Burns, GP; De Soyza, A
Abstract : Introduction: Anxiety and depression are common co-morbidities in COPD. Anxiety is associated with increased breathlessness, lower levels of self-efficacy, impaired health status, poorer treatment outcomes and reduced survival, increased risk of hospitalisation, longer in-patient stay, readmissions and unhealthy behaviours such as smoking and lack of exercise. The aim of this abstract is to present prevalence data, engagement and baseline patient characteristics from the largest RCT on CBT in COPD. Study design: A multicentre RCT with follow up at 3, 6 and 12 months (ISCRCTN55206395). Outcome measures include mean HADS-A (anxiety) and HADS-D (depression) score, 1 EuroQol -5D Questionnaire, 2 COPD Clinical Assessment Tool 3 and admission prevention at three, six and 12 months post intervention. Approach: 1, 518 patients were screened for symptoms of anxiety using the Hospital Anxiety and Depression Scale (HADS). Two thirds, 705 (59%) patients scored ≥8 for anxiety and were approached. Intervention: Up to 6 CBT sessions provided by one of four respiratory nurses were offered. Self-help leaflets on anxiety and depression were provided as standard care. Usual care: Self- help leaflets only. Results: 42% of eligible patients consented to take part. Groups were well matched at baseline (Table 1) with no correlation between FEV1 and anxiety. A median of 4 CBT sessions (range 2–6) was delivered. Retention was high: 85% at 3 months and 72% at 6 months. Conclusion: The prevalence of anxiety and depression is high in patients with COPD and screening is therefore recommended. Affected patients were willing to engage in CBT in this large study. Results from 3, 6 and 12 months data will be will be available in November 2015 and will be reported. Results will include the cost effectiveness of CBT in COPD delivered by respiratory nurses. Funding: NIHR fellowship. References: 1 Zigmond AS, Snaith RP. The hospital anxiety and depression scale. Acta Psychiatr Scand . 1983;67 (6):361–370 2 EQ-5D. www.euroqol.org/about-eq5d/how-to-use-eq-5d.html . Accessed 11.4.2015 3 Jone PW, Harding G, Berry P, Wiklund I, Chen WH, Kline LN. Development and first validation of the COPD Assessment Test. Eur Respir J . 2009;34 (3):648–654